Association of p53 codon 72 polymorphism and survival of North Indian lung cancer patients treated with platinum-based chemotherapy - Kumari, Ankita; Bahl, Charu; Singh, Navneet; Behera, Digambar; Sharma, Siddharth (Molecular biology reports, 2016)
p 53 helps in maintaining genomic stability by undergoing cellular arrest, DNA repair or cellular apoptosis during DNA damage. So, as to find the association of p 53 Arg 72 Pro towards lung carcinogenesis and overall survival of North Indian lung cancer patients, single nucleotide polymorphic variant (rs1042522) was analyzed. 840 subjects including 420 cases and 420 controls were recruited and genotyped using PCR-RFLP technique for p 53 Arg 72 Pro polymorphic site. Association was analyzed using adjusted odds ratio along with its confidence intervals (95 % CI) and p value predicted from logistic regression whereas overall survival for lung cancer patients was obtained using Kaplan–Meir and Cox regression model for different parameters to obtain hazard ratio and survival time with statistical significance (log-rank p value). None of the variant genotypes for p 53 Arg 72 Pro showed any association towards lung cancer risk or any specific histological subtype. Lung cancer subjects with Pro / Pro genotype had better median survival time as compared to Arg / Pro genotype (10 months; HR = 0.65; 95 % CI = 0.45–0.95; p = 0.03). Furthermore, female lung cancer patients with Arg / Pro (HR = 0.08; 95 % CI = 0.02–0.34; p = 0.0005) and Pro / Pro (HR = 0.21; 95 % CI = 0.06–0.67; p = 0.008) genotypes showed a better overall survival and hence a better prognosis as compared to males. Our data also reveals that lung cancer patients with ECOG scores between 0 and 1 and carrying the Pro / Pro had better chances of survival. p 53 codon 72 polymorphism could play a role as a prognostic marker in lung cancer patients.